H2+ in a weak magnetic field. (22nd January 2015) - Cobaxin, Héctor Medel; Alijah, Alexander; Vieyra, Juan Carlos López; Turbiner, Alexander V
Abstract: The electronic energy of in magnetic fields of up to (or T) is investigated. Numerical values of the magnetic susceptibility for both the diamagnetic and paramagnetic contributions are reported for arbitrary orientations of the molecule in the magnetic field. It is shown that both diamagnetic and paramagnetic susceptibilities grow with inclination, while paramagnetic susceptibility is systematically much smaller than the diamagnetic one. Accurate two-dimensional Born–Oppenheimer surfaces are obtained with special trial functions. Using these surfaces, vibrational and rotational states are computed and analyzed for the isotopologues and .